THE IMPACT OF ONLINE VISUAL MERCHANDISING AND AFFILIATE MARKETING FOR CLOTHING PRODUCT ON SHOPEE CUSTOMER PURCHASE DECISION - Makagansa, Meveri Cyanli; Pandowo, Merinda H.C.; Wangke, Shinta J.C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The increasing growth of digital platforms, or e-commerce, which is naturally accompanied by the increasing number of online stores that are present on each e-commerce platform. This study is intended to identify the influence of Visual Merchandising and Affiliate Marketing on Shopee Customer Purchase Decision, both partially and silmutaneously.  The population is the customers of Shopee as many as 100 respondents through random sampling technique and analysed with Multiple Regression Analysis Method. The results show that Affiliate Marketing has a significant impact on Shopee customer purchase decisions for clothing products, while Online Visual Merchandising, though positively related, does not show a statistically significant effect. It is recommended that marketers should prioritize Affiliate Marketing strategies on Shopee to effectively drive customer purchases, while Online Visual Merhcandising may serve a supportive role.   Keywords: Online Visual Merchandising, Affiliate Marketing, Customer Purchase Decision